Arte, conhecimento e verdade do pensamento do jovem Nietzsche - Ricardo Jose Camelo da Silva (2003)
This dissertation tries to make an approach on youngNietzsches reflections about art. In our study, we intended to detailthe relationship between art and knowledge, art and truth. At first,we have analysed the connection between art and knowledge throughelements from Greek culture. In a second moment, we analysed languageformation and the connections between art and truth. Our intention, ina sense, is to demonstre the importance of art in Nietzsches earlierworks.